Risk Mitigation of Notarial Practical Through The Notary Responsibility Release Clause - Diana, Yessica (Faculty of Law, Universitas Pekalongan, 2024)
The widespread of notary criminalization recently proves legal protection for notary in Indonesia is still unstable. One risk mitigation that could be used to emphasize it is by implementing the Notary Responsibility Release Clause in each created deed. Therefore, the research is needed regarding the implications of applying the Notary Responsibility Release Clause to ensure a consistent understanding of law enforcement in Indonesia. The purpose of the research is to elevate the issue of how the implications of the Notary Responsibility Release Clause should be interpreted and fully applied, especially in notarial practical and generally in law enforcement practices in Indonesia. The research method in this article is doctrinal. The research typology is descriptive-analytical research using secondary data through document study. This research aims to find the necessity of implementing the Notary Responsibility Release Clause as legal protection for notary whose duties are based on good faith, the rule of law, and professional ethics. Also, it creates clear limitations regarding the notary's responsibility in facing demands or legal claims caused by notary act based on good faith yet causing unintended consequences for the client. Thus, a good faith notary could be protected in fulfilling their official duties.